Strategic Implementation of The Langkawi Tourism Blueprint 2011-2015 : A case study - Sijabat, Ferdi Nazirun; Arshad, Darwina Arshad (JOURNAL OF ECONOMIC SCIENCE, 2015)
The successful of tourism industry affects positively to the future growth of world tourism market. It is viewed as the source of promising economic benefit to the host country. Therefore tourism development is acknowledged as a mean to spur countries economic, due to the ability of the sector to raise job creation, standard of living and upgrade the infrastructure. This study aims to describe the progress of the Langkawi Tourism Blueprint 2011-2015 implementation and the collaboration among agencies in order to achieve the main objectives of the blueprint that is to enlist Langkawi at the top ten tourism island and eco-tourism in the world. The study applied case study method, where data was collected through interview, archives record and official reports. The findings of the study revealed that the implementation of the blueprintâs initiatives was at 73 percent by November 2012. This initiative proved the increment of tourist arrival into Langkawi which totaled sum of 3 million tourists. Hence, Delivery Management Office (DMO) of Langkawi Development Authority (LADA) plays critical role to monitor and control the implementation of the blueprint. It is expected that by 2015, Langkawi becomes one of the greatest destination Island and eco-tourism in the world as stated in the Langkawi Tourism Blueprint.